Social innovations and drivers in flood early warning systems: A community-based transboundary perspective from Elegu flood plain in Northern Uganda - Canwat, Vincent (My University, 2023)
Early warning systems play significant roles in disaster risk reduction and management. However, a global picture of how they function on the ground, especially in developing countries, is lacking. This study assessed social innovations and drivers in the community-based transboundary flood early warning systems in the Ugandan context. The study found that the community-based transboundary flood early warning system generated three social innovations: new inter-community relations, new community-local resource relations, and new housing and bedding structures. New intercommunity relations were driven by the transboundary nature of the flood and kinship. New community-local resource relations were driven by the lack of government support for the early warning system. New housing and bedding structures were driven by the uncertainty about the flood at night. The study confirms the importance of social market failure in driving social innovations and the role of community-based flood early warning systems in promoting the utilisation of local resources. The effectiveness of transboundary early warning systems in extending lead time and reducing losses was also confirmed. However, the early warning system was found to be effective only during day time. The study, therefore, recommends government intervention in bridging the early warning system gap by installing telemetry.
Keywords: community-based early warning system, early warning systems, Elegu Flood Plain, flood,GIS, Social innovations, transboundary early warning system, Uganda